Penerapan Asas Konsensualisme Dalam E-Payment Berbasis Qris - Ariyanto; Naim, Faghlaifi; Qubbaja, Adnan (Jurnal Hukum IUS QUIA IUSTUM, 2025)
QRIS-based e-Payment has changed the way of modern payments with its convenience and efficiency. However, concerns have arisen about the protection of personal data and the principle of consent in these transactions. The principle of consent on the other hand is a major concern as it requires clear and voluntary consent in data collection and processing, but QRIS-based transactions often do not meet this standard since the information provided is less transparent to users. Current legal regulations such as the Civil Code have not been fully able to address the protection of personal data and electronic transactions that are increasingly common. In response to these existing issues, this study examines the protection of the principle of consent in transactions using QRIS and voices the need for legal adaptation that is more relevant to the latest technology. The formulation of the problem contained in this study is: First, What information is transmitted by the payment method through QRIS generally in digital transactions? Second, How is the Application of the Principle of Consent in the Agreement on Information Given in QR-Code Transactions. The research method used is the normative juridical method with a statutory approach by examining relevant regulations. Research results: First, the transmitted data such as user identity, payment amount, date and time, transaction reference number, transaction description, merchant code, merchant name and identity, and payment account information. Second, from the perspective of the principle of consent, it emphasizes the existence of an agreement or meeting of mind between the parties which is implemented through the offer and acceptance of QR codes, approval of information, intention to be bound by the transaction and have the same understanding to carry out the transaction.Keywords: E-Payment, QRIS, principle of consent AbstrakE-Payment berbasis QRIS telah mengubah cara pembayaran modern dengan kemudahan dan efisiensinya. Namun, muncul perhatian tentang perlindungan data pribadi dan asas konsensualisme dalam transaksi ini. Asas konsensualisme di sisi lain juga menjadi perhatian utama karena memerlukan persetujuan jelas dan suka rela dalam pengumpulan dan pengolahan data, namun transaksi berbasis QRIS sering tidak memenuhi standar ini dengan informasi yang kurang transparan bagi pengguna. Aturan hukum saat ini seperti KUHPerdata belum sepenuhnya mampu mengatasi perlindungan data pribadi dan transaksi elektronik yang semakin umum terjadi. Dalam menyikapi isu yang ada, penelitian ini mengkaji perlindungan asas konsensualisme dalam transaksi menggunakan QRIS serta menyuarakan perlunya adaptasi hukum yang lebih relevan dengan teknologi mutakhir. Rumusan masalah dalam penelitian ini adalah: Pertama, Apa saja informasi yang ditransmisikan oleh metode pembayaran melalu QRIS umumnya pada transaksi digital? Kedua, Bagaimana Penerapan Asas Konsualisme Dalam Kesepakatan Informasi Yang Diberikan Dalam Transaksi QR-Code. Metode penelitian yang digunakan dalah metode yuridis normatif dengan pendekatan perundang-undangan dengan mengkaji peraturan-peraturan yang relevan. Hasil penelitian: Pertama, data yang ditransmisikan seperti identitas pengguna, jumlah pembayaran, tanggal dan waktu, nomor referensi transaksi, deskripsi transaksi, kode merchant, nama dan identitas merchant, serta informasi rekening pembayaran. Kedua, pada perspektif asas konsensualisme, menekankan pada adanya kesepakatan atau meeting of mind antara para pihak yang diterapkan melalui penawaran dan penerimaan QR code, persetujuan atas informasi, niat untuk terikat dalam transaksi dan memiliki kesepahaman yang sama untuk melakukan transaksi.Kata Kunci: E-Payment, QRIS, asas konsensualisme